Factors Associated with Hypertension among Elderly in Medan, Indonesia - Santa Ulina Apriani Situngkir; Namora Lumongga Lubis; Fazidah Aguslina Siregar (Journal of Epidemiology and Public Health, 2019)
Background: Hypertension or high blood pressure is often called the silent killer. World Health Organization reported that hypertension is estimated to cause 7.5 million deaths (12.8% of the total of all deaths). Prevalence of hypertension in Medan ranked the third in Indonesia in all ages with the mortality of 6.8%. The purpose of this study was to examine factors associated with hyper